Not just the lack of food - Mata Jiménez, Leonardo (1977)
Whose who are familiar with rural areas of developing nations are often amazed to tind malnourished children in families where food is available in amounts sufficient to ensure an adequate diet. There may seem to be plenty of food in the house and, quite strikingly, the mother of the malnourished child, as well as other adults, may appear well nourished, or even overweight. Health workers ask themselves why malnutrition does not affect more children when there is widespread food shortage. In low-income families, with deficient education and living under unsanitary conditions, malnutrition occurs only in certain children. The distribution of malnutrition in today's world reveals a distinct concentration of endemic foci in the tropical and sub-tropical regions. Yet in some of these areas an excess production of proteins and calories is often recorded. In Central America, for example, acute malnutrition may appear in villages at times of abundance instead of when food is scarce, contrary to what might be expected from a simple cause-effect relationship between lack of food and malnutrition. The occurrence of severe malnutrition in such cases follows epidemics of infectious diseases, and indicates the relevance of such conditions in the genesis of nutritional disease. It is apparent that non-food factors playa definite role in the occurrence of malnutrition. Epidemiological studies help to pinpoint these factors, which may conveniently be divided into the chemical, the biological and the sociocultural environments. Environmental forces act more strongly on human society in the tropics and sub-tropics, retarding or preventing its development. It is in these areas that the interaction of physico-chemical, biological and sociocultural factors intensifies and tends to favour the occurrence of malnutrition.